Establishing Justice in Middle America : A History of the United States Court of Appeals for the Eighth Circuit - Morris, Jeffrey B. (Jeffrey Brandon), 1941- (Book collections on Project MUSE., 2007)
Headquartered in St. Louis and serving primarily Midwestern states, the Eighth Circuit Court has ruled on cases that touch some of the most significant issues in American history, including Native American rights, school segregation, and abortion. Jeffrey Brandon Morris covers this courts history, revealing how, in many ways, the history of a regional court is a history of the nation itself.